Implementing Just Culture for Patient Safety Incident Management in Mental Hospitals: An HRM Perspective - Dedi Nurhasan Ashari; Ernani Hadiyati; Gunadi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study explores nurses’ experiences following patient safety incidents and the implementation of a just culture in mental hospitals from a human resource management perspective. A qualitative phenomenological approach was used through in-depth interviews with 12 nurses and thematic analysis. The findings show that patient safety incidents cause anxiety, guilt, fear, and emotional distress while encouraging professional reflection and increased vigilance. Just culture was perceived as a constructive and non-punitive approach that emphasizes balanced accountability between individual and system factors. Organizational support, workload management, workforce planning, and continuous patient safety training were identified as essential strategies for reducing post-incident impacts. The study concludes that integrating a just culture with human resource management practices supports organizational learning and sustainable patient safety improvement. However, the qualitative design, limited number of participants, and single-hospital setting may restrict generalizability. This study contributes to the understanding of post-incident nursing management through organizational support and learning-oriented approaches.